Spin-flop and magnetodielectric reversal in Yb substituted GdMnO3. (23rd February 2018) - Pal, A; Prellier, W; Murugavel, P
Abstract: The evolution of various spin structures in Yb doped GdMnO3 distorted orthorhombic perovskite system was investigated from their magnetic, dielectric and magnetodielectric characteristics. The Gd1− x Yb x MnO3 (0 ⩽ x ⩽ 0.15) revealed an enhanced magnetodielectric coupling when their magnetic structure is guided from ab to the bc -cycloidal spin structure upon Yb doping. The compounds exhibit magnetic field and temperature controlled spin-flop from c to a -axis. Additionally, magnetodielectric reversal is observed for the x = 0.1 sample which depends on both magnetic field and temperature. The resultant correlation between magnetic and electric orderings is discussed in the frame of symmetric and antisymmetric exchange interaction models. These findings provide further insight in understanding the magnetoelectric materials and importantly show a way to tune the magnetic and magnetodielectric properties towards better application potential.